Suitability of Tree Species in an Agroforestry System in Hill Zone of Karnataka - Patil, S. J.; Nadagoudar, B. S.; Mutanal, S. M.; Madiwalar, S. L.; Devaranavadgi, S. B. (Indian Forester, 2000)
An experiment involving arable crops (paddy, maize, sunhemp), silvicultural crops (E. tereticornis, C. equisetifolia, A. molucana, T. grandis, D. sissoo), horticultural crop (Sapota) and pasture (grass) was initiated in clayey soils of Prabhunagar, Dharwad during 1976. Sapota was planted at 10 m apart and three trees were planted in between 2 Sapota plants. Grass was planted in 1 m wide strip on either side of Sapota+tree species. At the end of 17 years the trees were felled. Among five trees studied, income from Teak was higher (Rs. 1,47,924/ha) followed by eucalyptus (Rs.67,883/ha), thus indicating Teak as the most suitable tree species for adopting Teak based agroforestry system of landuse in hill zone of Karnataka. Total income from field crops+Sapota+Teak was 46 per cent higher than growing field crops+Sapota.